Development of Professional and Pedagogical Skills of Future Teachers on the Basis of an Innovative Approach - Mirzaeva Zubayda Ashurovna (Researchparks Publishing, 2023)
This article describes the conceptual approaches to improving the methodological competence of future teachers and its specific features. It was emphasized that the individual-oriented, activity-oriented and differentiated approaches to determining the components of methodical competence of future teachers are important.